Analysis of Health-Seeking Behavior for Non-communicable Diseases: a Literature Review - Lu'lu Luthfiatun Ulinnuha; Titih Huriah (Journal of Public Health Sciences, 2025)
People's behavior in seeking health care is an important first step in preventing and controlling non-communicable diseases (NCDs). Non-communicable diseases account for 43 million deaths globally, with 82% of these premature deaths occurring in low- and middle-income countries. Therefore, this literature review aims to explore patterns of health-seeking behavior and the factors that influence them worldwide. This research employed a literature review method, with data searches conducted through Emerald Insight, PubMed, and Scopus, following the PRISMA protocol guidelines for literature reviews. The keywords used in the search strategy were "health-seeking behavior" and "non-communicable disease" combined using Boolean operators AND and OR. Seven international articles published between 2019 and 2024 met the inclusion and exclusion criteria. The findings of this research indicate that health-seeking behavior for non-communicable diseases varies significantly across countries, with a preference for traditional medicine remaining prevalent. Social, cultural, economic, and health services access factors influence this preference. Policymakers and relevant stakeholders should encourage promoting health-seeking behavior, expanding health insurance coverage, and strengthening healthcare infrastructure.